2008
DOI: 10.1016/j.ijsu.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ventral hernia repair. Our experience of 61 consecutive series: Prospective study

Abstract: Laparoscopic ventral hernia repair is feasible, safe and associated with an acceptable rate of complications. Laparoscopic ventral hernia repair can be performed as short stay surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In agreement with our result Hussain et al found that most common type of primary ventral hernia was para umbilical hernia (42%), Umbilical (39.34%), Spigelian hernia and Epigastric hernia (6.55%) [8].…”
Section: Lwsupporting
confidence: 93%
“…In agreement with our result Hussain et al found that most common type of primary ventral hernia was para umbilical hernia (42%), Umbilical (39.34%), Spigelian hernia and Epigastric hernia (6.55%) [8].…”
Section: Lwsupporting
confidence: 93%
“…Also, it will abolish the risk of trocar-site incisional hernia as the mesh will be fitted to patch the defect in the abdominal wall, which constitutes the site of the original incisional hernia, and this is the same pathway where the trocar was introduced to the peritoneal cavity. We have published our technique and outcomes of our series in the International Journal of Surgery and the Journal of the Society of Laparoscopic Surgeons [2,3].…”
Section: Dear Editormentioning
confidence: 99%
“…In present study all wound infections are superficial. 19,20 only one patient has post-op wound infection present 4.7% which comparably less than study of Mike et al 7.6%, Ujiki et al 5% and Colon et al 4% thus it is comparable. [15][16][17] Seroma at postoperative day 7 was present in 2 patients that is 9.5% in present study compare to Mike et al, Ujiki et al, Lau et al was 20%, 13% and 7.6% respectively.…”
Section: Discussionmentioning
confidence: 54%